(untitled) (REMUNOM, 2025)
Health promotion through education is essential in Primary Health Care (PHC), especially when developed interdisciplinarily and focused on local realities. This study aims to report the experience of the "Hortiviva" project, carried out by residents of the Family Health Residency Program at the State University of Piauí, working with family gardeners linked to a community garden in the northern region of Teresina, Piauí. This is an experience report with a qualitative approach, developed between April and December 2024, through monthly meetings attended by 15 to 30 workers. The activities were planned and implemented by a multidisciplinary team, using active methodologies such as discussion groups, educational games, and group dynamics. The topics covered included mental health, chronic disease prevention, healthy eating, integrative practices, and quality of life. The results showed that the community garden has established itself as a space for therapy, socialization, income generation, and well-being. The strengthening of the bond between professionals and the community, the appreciation of popular knowledge, and the encouragement of participants’ autonomy were observed. For residents, the experience fostered critical reflections on healthcare, interdisciplinarity, and humane practices. The conclusion is that projects like "Hortiviva" strengthen PHC by integrating health, territory, and social participation, promoting positive transformations in community life.